2019
DOI: 10.1073/pnas.1907852116
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the allosteric coupling mechanism in a glutamate transporter homolog via unnatural amino acid mutagenesis

Abstract: Glutamate transporters harness the ionic gradients across cell membranes for the concentrative uptake of glutamate. The sodium-coupled Asp symporter, GltPh is an archaeal homolog of glutamate transporters and has been extensively used to understand the transport mechanism. A critical aspect of the transport cycle in GltPh is the coupled binding of sodium and aspartate. Previous studies have suggested a major role for hairpin-2 (HP2), which functions as the extracellular gate for the aspartate binding site, in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
47
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(49 citation statements)
references
References 43 publications
2
47
0
Order By: Relevance
“…However, this cooperativity is greatly suppressed when Met314 (Met311 in Glt Ph ) is replaced by Ala or Leu [37], as is the substrate affinity. Although no structures have been reported for any of these mutants, Trp fluorescence measurements show that the pattern of conformational changes in HP2 in response to ion and substrate binding [19,37] is also subtly altered upon mutation of Met314 [38,39].…”
Section: Introductionmentioning
confidence: 96%
“…However, this cooperativity is greatly suppressed when Met314 (Met311 in Glt Ph ) is replaced by Ala or Leu [37], as is the substrate affinity. Although no structures have been reported for any of these mutants, Trp fluorescence measurements show that the pattern of conformational changes in HP2 in response to ion and substrate binding [19,37] is also subtly altered upon mutation of Met314 [38,39].…”
Section: Introductionmentioning
confidence: 96%
“…Gating in the OFS, where only HP2 moves to bind Na + ions and L-asp is faster (Hanelt et al, 2015), although slow HP2 opening has also been proposed (Riederer and Valiyaveetil, 2019). Notably, kinetic studies showed that the release (and binding) of one Na + ion in the IFS, most likely Na2, is rapid (Oh and Boudker, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…These extensive conformational changes, involving repacking the domain interface, may explain why substrate gating is slow in the IFS ( Oh and Boudker, 2018 ). Gating in the OFS, where only HP2 moves to bind Na + ions and L-asp is faster ( Hänelt et al, 2015 ), although slow HP2 opening has also been proposed ( Riederer and Valiyaveetil, 2019 ). Notably, kinetic studies showed that the release (and binding) of one Na + ion in the IFS, most likely Na2, is rapid ( Oh and Boudker, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As the transport domain translocates into the IFS, HP2 replaces HP1 on the domains interface, while HP1 now lines an intracellular vestibule leading to the substrate-binding site (Figure 1 Supplementary Figure 1). Structural and biophysical studies have established that HP2 serves as the extracellular gate of the transporter (Boudker et al, 2007;Focke et al, 2011;Verdon et al, 2014;Riederer e Valiyaveetil, 2019). HP2 closes when the transporter is bound to Na + ions and L-asp and when it is empty (Yernool et al, 2004;Jensen et al, 2013;Verdon et al, 2014).…”
mentioning
confidence: 99%